Reflecting Intergenerational Communication through Turn-Taking Strategies, Conveyed in Mata Najwa Talk Show - Firdausiyah, Hurrotul (Research Community for Critical Society and Environment, 2025)
This research examines how generational differences are reflected in conversational interactions, particularly in turn-taking behavior in public discourse. As intergenerational communication becomes increasingly common in the media, differences in communication styles often lead to misunderstandings, misinterpretations, or perceived power imbalances. This research investigates turn-taking strategies used by boomers, Gen X, millennials, and Gen Z in the Mata Najwa talk show episode '4 Generasi Bicara Generation Gap'. The data were the utterances of Slamet Rahardjo Djarot (as a boomer), Panji Pragiwaksono (as a Gen X), Felicia Putri Tjiasaka (as a millennial), and Muharam Fachri (as a Gen Z). The data were taken from Mata Najwa's talk show '4 Generasi Bicara Generation Gap' episode on Najwa Shihab's YouTube channel. Then, the data were analyzed using Stenstrom's turn-taking theory to achieve the goal. The results revealed that boomers, Gen X, millennials, and Gen Z use similar turn-taking strategies, namely taking the turn, holding the turn, and yielding the turn. However, they have different sub-strategies and different ways to take the turn, to hold the turn, and to yield the turn. The most dominant strategy used by all generations is to take the turn. This strategy is used by them when they want to evaluate the previous speaker before expressing their opinion. This talk show is dominated by discussion, so the uptake strategy is relevant for all generations during the conversations. This finding suggests that intergenerational communication in media spaces is characterized by responsiveness and dialogue, rather than dominance. The uptake strategy reflects a communicative norm that emphasizes attentiveness, evaluation, and mutual respect, as reflected in broader social expectations in today's public discourse.